Atomic-scale study on incoherent twin boundary evolution in nanograined Cu. (September 2020) - Zhang, Yong; Guo, Jinming; Ming, Wenquan; Chen, Jianghua; Zhang, Zaoli
Abstract: Via in-situ experiments, we show the atomic-scale evolution of incoherent twin boundary (ITB) into a high-angle grain boundary (HAGB). We find that the electron-beam can activate the motion of Shockley partials, which causes detwinning and formation of segmented ITB (sITB). Consequently, a series of step-like extended dislocations are further produced along the sITB due to the Shockley partial cross-slip on two intersecting {111} planes. This process results in an unfixed misorientation (<18°) between the original twins and the un-detwinned parts, and further converts the sITB into a HAGB. The study offers insights into the atomic-scale grain refinement in nano-twinned materials. Graphical abstract: Image, graphical abstract